2010
DOI: 10.1128/aem.02740-09
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Attachment of the Deoxysugar Moiety and Assembly of the Gene Cluster for Caprazamycin Biosynthesis

Abstract: Caprazamycins are antimycobacterials produced by Streptomyces sp. MK730-62F2. Previously, cosmid cpzLK09 was shown to direct the biosynthesis of caprazamycin aglycones, but not of intact caprazamycins. Sequence analysis of cpzLK09 identified 23 genes involved in the formation of the caprazamycin aglycones and the transfer and methylation of the sugar moiety, together with genes for resistance, transport, and regulation. In this study, coexpression of cpzLK09 in Streptomyces coelicolor M512 with pRHAM, containi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…MK730‐62F2, all genes required for the biosynthesis of the caprazamycin aglycones are localized in a contiguous gene cluster comprising 23 open reading frames that span ∼26 kb. In contrast, the genes for the biosynthesis of the L ‐rhamnose moiety are located elsewhere in the genome 34. Integration of cosmid cpzLK09, comprising the caprazamycin gene cluster, into the ΦC31 attachment site of S. coelicolor M512 therefore led to the formation of caprazamycin aglycones in the resulting strains.…”
Section: Resultsmentioning
confidence: 99%
“…MK730‐62F2, all genes required for the biosynthesis of the caprazamycin aglycones are localized in a contiguous gene cluster comprising 23 open reading frames that span ∼26 kb. In contrast, the genes for the biosynthesis of the L ‐rhamnose moiety are located elsewhere in the genome 34. Integration of cosmid cpzLK09, comprising the caprazamycin gene cluster, into the ΦC31 attachment site of S. coelicolor M512 therefore led to the formation of caprazamycin aglycones in the resulting strains.…”
Section: Resultsmentioning
confidence: 99%
“…[13] Structureactivity studies with synthesised peptidyl nucleoside analogues revealed that the terminal amino group, the N-methyl-Daba and probably the uridine moiety are most important for the inhibition of translocase I. [14,15] Recently, the identification and analysis of the gene clusters for caprazamycins, [16,17] liposidomycins [18][19][20] and capuramycintype A-500359 [21] has given the first insights into the biosynthesis of the structurally unusual nucleoside antibiotics that target translocase I. However, little is known about the formation of the uridylpeptide-type translocase I inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…MK730-62F2 for heterologous expression. This strain is known to provide activated l -rhamnose for the endogenous production of caprazamycins and the respective deoxysugar biosynthesis genes have recently been identified 18,19. To our satisfaction, LC-MS analysis of culture extracts from the heterologous mutant showed the production of a single new peak with a mass, retention time and UV-spectrum identical to a commercial standard of 1 (Fig.…”
Section: Resultsmentioning
confidence: 64%